Topology of non-inductive DC/DC converters with galvanic isolated circuits - V. P. Babenko; V. K. Bityukov (Российский технологический журнал)
Non-inductive (throttle-free) DC/DC converters are used in low-power and highly integrated electronic systems. A circuit analysis of the basic topologies of non-inductive DC/DC charge-pumped converters which perform typical DC-voltage conversions, i.e., lowering, raising and inverting, was carried out. The galvanic isolation between the input and output circuits of the converter was achieved even in the integrated version due to forming a time delay of the switches (Dead Time, DT), commuting a “flying” capacitor, which is transferring the charge to the storage capacitor and the load. A circuit of the DT driver was developed and its parameters, at which the through-current flow in the switch is prevented and the conditions of galvanic isolation of the input and output circuits are satisfied, were studied. The simulation was built with a popular Electronics Workbench software, widely used in training of specialists in radio electronics at higher educational institutions. The results of the study of the basic power characteristics of DC/DC conversion, such as output current and voltage, voltage transfer coefficient, efficiency, output equivalent resistance, were presented. The efficiency of conversion was estimated by varying the capacities of the “flying” and storage capacitors, the resistance of the switches in the closed state, and the frequency of switching. It is proved that the charge pumping method is simple and effective at low load currents (mA units), when both the voltage transfer coefficient from input to output and efficiency are high, and are approaching to “one”. However, with the increase of the load current, the voltage transfer coefficient and efficiency decrease, the output voltage ripples increase.